"Always on the go": A qualitative study of the perceptions of cardiovascular disease risk among Latino cab drivers. Issue 12 (10th September 2019) - Orleans, Rachel; Boutin‐Foster, Carla; Scott, Ebony; Ramos, Rosio; Faussett, Zenobia; Lata Armijos, Jorge D.
Abstract: Background: The taxicab industry is a burgeoning occupation that predominantly employs immigrant males from low socioeconomic backgrounds. Factors such as sedentary nature, environmental factors, high stress coupled with socioeconomic factors may increase cardiovascular disease risk among taxicab drivers. Latinos, a growing immigrant population make up approximately 20% of this industry. However, few studies focus on their experiences as cab drivers or on the factors that may increase their cardiovascular risks. Methods: This was an ethnographic qualitative study. Data was collected via individual interviews combined with Go‐Alongs. The Go‐Along is an observational qualitative method whereby researchers accompany participants during routine activities and make observations. Interviews and observations were transcribed and coded to identify emerging themes. Results: Thirty‐two Latino male cab drivers participated; their mean age was 45 + 12 years; 47% did not finish high school; and 63% earned $30 000 or less. Time and stress emerged as dominant themes. Time constraints posed a barrier to healthy eating and physical activity. Drivers reported stress from constantly worrying about their finances and personal safety. Drivers also described stress from the physical toll of driving on the body. Go‐Alongs supported these themes and identified social interactions and environmental factors that could be leveraged for health promotion. Conclusions: This study provided an opportunity for cab drivers to describe their perspectives on reasons why their occupation was associated with a high risk for cardiovascular disease. The Go‐Alongs contributed to the understanding of the social and environmental context that characterized cardiovascular risks in this occupation.